Ibn Khaldun's Epistemological and Methodological Views of History - Mahdi Frahani Monfared (تاریخ اسلام, 2003)
Abd ar ه Rahman Ibn Khaldun is known as the father of philosophy and history. For most of researchers who have studied Ibn Khaldun's thought, his views in theoretical philosophy and history have been more attractive. A thorough study of his Mughaddimah reveals that in addition to presenting a theoretical system to investigate the development of human communities, Ibn Khaldun offers other views that are worthy of serious attention in philosophy of history, or rather critical philosophy of history. This paper's objective is to propose that the first signs of Such discussions as critical history, historical sociology, and historical psychology can be traced back to and recognized in Ibn Khaldun's Mughaddimah.